(untitled) (Research, Society and Development, 2022)
Youth is a period of change and adaptation. Pregnancy at this stage of life is the result of the exercise of sexuality and it is seen as a social problem. Fatherhood occurs in this scenario being influenced by culturally constructed gender issues. The health services, by turn their assistance to the maternal and child public, reproduce this social scenario, this way it is essential to include the father in the context of pregnancy and the recognition of the importance of his participation in prenatal care and childbirth. Objective: to describe the experience of young parents in prenatal care and in the childbirth of their first Method: qualitative study, done by a semi-structured interview with twelve young parents, selected by the snowball technique. Content analysis was used to process the data treatment. Results: the mosct young people showed limited knowledge about prenatal care, had passive participation during consultations or stayed outside the office. Only one father experienced the birth of his son. Conclusion: gender roles, linked to masculinity, which negatively influence the exercise of fatherhood, need to be rethought and re-elaborated, and interdisciplinary and intersectoral actions that problematize these issues must be aimed at men throughout their life cycle.